Aqueous carbon coating slurry and carbon coated aluminum foil and method for producing the same

CN121249217BActive Publication Date: 2026-10-30合肥源元科技股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511338047.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-18
Publication Date
2026-10-30
Estimated Expiration
2045-09-18

AI Technical Summary

Technical Problem

[0003]然而,水性体系的应用面临一系列技术瓶颈:例如导电网络构建难、界面结合力弱、浆料稳定性差以及综合性能平衡难等问题很大程度限制了涂碳铝箔的发展

Benefits of technology

本发明中三元导电复配(炭黑A+炭黑B+石墨)体系构筑高效三维导电网络,配和两种分散剂进行固体份分散优化,实现涂碳铝箔的超低电阻。超支化聚酯胺和改性聚丙烯酸同时具有强分散、长效稳定、提升界面粘结的能力,它们其独特的支化结构与多重官能团,协同解决了水性体系中导电组分分散难、浆料易沉降、涂层附着力弱这三大痛点,确保了其超高剥离强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121249217B_ABST
    Figure CN121249217B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium batteries, and particularly discloses a water-based carbon-coating slurry, a carbon-coating aluminum foil and a preparation method thereof. The water-based carbon-coating slurry is prepared from the following components in parts by weight: 0.3-0.6 parts of conductive graphite, 3-6 parts of conductive carbon black, 20-40 parts of modified polyacrylic acid, 0.1-0.5 parts of hyperbranched polyether amine dispersant, 0.1-1 parts of sulfonate dispersant, 20-40 parts of auxiliary agent and 30-40.5 parts of solvent. The conductive carbon black comprises carbon black A and carbon black B, the oil absorption value of the carbon black A is 180-210 mL / 100g, and the oil absorption value of the carbon black B is 230-260 mL / 100g. In the application, a ternary conductive compound (carbon black A+carbon black B+graphite) system is used to construct an efficient three-dimensional conductive network, two kinds of dispersants are used for solid content dispersion optimization, the ultra-low resistance of the carbon-coating aluminum foil is realized, the perfect unity of high conductivity, high peeling strength, excellent dispersion stability and environmental protection is realized, and a key current collector material solution scheme for high-performance lithium ion batteries is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, and in particular to an aqueous carbon-coated slurry and a carbon-coated aluminum foil and a method for preparing the same. Background Technology

[0002] As a core power source in the new energy field, the performance improvement of lithium-ion batteries highly depends on the innovation of key materials. Carbon-coated aluminum foil, as a positive electrode current collector material, significantly reduces interfacial contact resistance, improves electron transport efficiency, enhances the adhesion of active materials, and inhibits aluminum foil corrosion by coating the aluminum foil surface with a conductive carbon layer. This is crucial for improving battery rate performance, cycle life, and safety. Currently, commercially available carbon-coating slurries mostly use organic solvent systems (such as NMP). While these achieve good conductivity and adhesion, they have significant drawbacks, including high volatile organic compound (VOC) emissions, significant environmental pollution, prominent production safety hazards, and high solvent recovery costs. With the increasing demand for sustainable development in the battery industry, developing a high-performance aqueous carbon-coating slurry has become an urgent technological transformation direction for the industry.

[0003] However, the application of aqueous systems faces a series of technical bottlenecks: for example, difficulties in constructing conductive networks, weak interfacial adhesion, poor slurry stability, and challenges in balancing overall performance greatly limit the development of carbon-coated aluminum foil. While some research exists on aqueous carbon-coated slurries, it largely focuses on single-component optimization or binary composites, offering limited effectiveness in resolving the core contradiction between "high conductivity" and "high peel strength," and particularly struggling to maintain long-term stable bonding between the coating and aluminum foil interface under harsh battery operating environments. Summary of the Invention

[0004] Based on this, the purpose of this invention is to provide an aqueous carbon-coated slurry and a carbon-coated aluminum foil and their preparation method, which achieves a perfect balance of high conductivity, high peel strength, excellent dispersion stability and environmental friendliness, providing a key current collector material solution for high-performance lithium-ion batteries.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides an aqueous carbon coating slurry, which is prepared from the following components in parts by weight: 0.3-0.6 parts conductive graphite, 3-6 parts conductive carbon black, 20-40 parts modified polyacrylic acid, 0.1-0.5 parts hyperbranched polyesteramine dispersant, 0.1-1 parts sulfonate dispersant, 20-40 parts additives, and 30-40.5 parts solvent; the conductive carbon black comprises carbon black A and carbon black B, wherein the oil absorption value of carbon black A is 180-210 mL / 100 g, and the oil absorption value of carbon black B is 230-260 mL / 100 g.

[0006] In this invention, a ternary conductive compound (carbon black A + carbon black B + graphite) system constructs a highly efficient three-dimensional conductive network. Two dispersants are used to optimize solid component dispersion, achieving ultra-low resistance in carbon-coated aluminum foil. Hyperbranched polyesteramine and modified polyacrylic acid simultaneously possess strong dispersing, long-term stability, and improved interfacial adhesion capabilities. Their unique branched structure and multiple functional groups synergistically solve three major pain points in aqueous systems: difficulty in dispersing conductive components, easy sedimentation of slurries, and weak coating adhesion, ensuring ultra-high peel strength.

[0007] As a further improvement to the above-described solution of the present invention, in the conductive carbon black, the weight ratio of carbon black A to carbon black B is 3:5-9. In the water-based carbon coating slurry, the mass ratio of conductive graphite to conductive carbon black is 1:(5-10).

[0008] As a further improvement to the above-described scheme of the present invention, the sulfonate dispersant is one of sodium p-styrene sulfonate, sodium dodecylbenzene sulfonate, and modified lignin sulfonate.

[0009] As a further improvement to the above-mentioned scheme of the present invention, the number average molecular weight of the hyperbranched polyesteramine dispersant is 2000-5000 g / mol.

[0010] As a further improvement to the above-described scheme of the present invention, the auxiliary agent is at least one of isopropanol and n-propanol; the solvent is deionized water, and the conductivity of deionized water is ≤20μm / cm. The water / alcohol system ensures environmental friendliness and process applicability.

[0011] As a further improvement to the above-mentioned solution of the present invention, the viscosity of the carbon coating slurry at 25°C is ≤300 mPa·s.

[0012] The present invention also provides a method for preparing the water-based carbon coating slurry as described above, which includes the following steps: S1. Add hyperbranched polyesteramine dispersant to deionized water and mix to obtain premix A; S2. Mix the additive with deionized water to obtain premixed solution B; S3. Add conductive graphite, conductive carbon black, modified polyacrylic acid, and sulfonate dispersant to deionized water, then add the premixed solution A, and mix evenly to obtain premixed solution C; S4. Add the premixed liquid B to the premixed liquid C, mix evenly, and grind for 2 hours to obtain an aqueous carbon coating slurry; In step S2, the amount of deionized water used accounts for 5% of the total amount of deionized water used; in step S3, the amount of deionized water used accounts for 45% of the total amount of deionized water used; and in step S3, the amount of deionized water used accounts for 50% of the total amount of deionized water used.

[0013] As a further improvement to the above-mentioned solution of the present invention, in step S4, the grinding is carried out using zirconia balls with a particle size of 0.3-0.5 mm as the grinding medium and at a rotation speed of 650-850 rpm.

[0014] The present invention also provides a carbon-coated aluminum foil, comprising a current collector and a coating disposed on at least one surface of the current collector, the coating being prepared from the aforementioned aqueous carbon-coating slurry, or from an aqueous carbon-coating slurry prepared by the aforementioned preparation method.

[0015] This invention also provides a method for preparing carbon-coated aluminum foil as described above, comprising the following steps: coating the aqueous carbon-coating slurry onto the surface of the corona-treated aluminum foil, with a coating thickness of 1-2 μm and an areal density ≤0.8 g / m². 2 Step drying is performed to obtain carbon-coated aluminum foil. The step drying process is as follows: first, infrared drying at 80-100℃ for 5-10 seconds, and then hot air drying at 120-150℃ for 10-15 seconds.

[0016] Compared with the prior art, the present invention has the following beneficial effects: In this invention, a ternary conductive compound (carbon black A + carbon black B + graphite) system constructs a highly efficient three-dimensional conductive network. Two dispersants are used to optimize solid component dispersion, achieving ultra-low resistance in carbon-coated aluminum foil. Hyperbranched polyesteramine and modified polyacrylic acid simultaneously possess strong dispersing, long-term stability, and improved interfacial adhesion capabilities. Their unique branched structure and multiple functional groups synergistically solve three major pain points in aqueous systems: difficulty in dispersing conductive components, easy sedimentation of slurries, and weak coating adhesion, ensuring ultra-high peel strength.

[0017] The conductive component of this invention exhibits excellent dispersibility under the combined action of modified acrylic resin and dispersant. Gradient drying further ensures uniform coating of the carbon layer, resulting in good overall performance. Moreover, the slurry mixing process of this invention is simple, achieving a perfect balance of high conductivity, high peel strength, excellent dispersion stability, and environmental friendliness, providing a key current collector material solution for high-performance lithium-ion batteries. Attached Figure Description

[0018] Figure 1 Settlement diagram of the water-based carbon coating slurry obtained in Example 3; Figure 2 The image shows the appearance of the carbon-coated aluminum foil obtained after the adhesion test in Example 3. Figure 3 The test image is obtained after the peel strength test in Example 3; Figure 4 The figure shows the results of room temperature cycling tests for the battery prepared in Example 3 and the aluminum foil. Detailed Implementation

[0019] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0021] Example 1 This embodiment proposes an aqueous carbon coating slurry, which comprises the following components in parts by weight: 0.5 parts conductive graphite, 5 parts conductive carbon black (wherein, the oil absorption value of carbon black A is 180mL / 100g, the oil absorption value of carbon black B is 260mL / 100g, and the amounts of carbon black A and carbon black B are 1.5 parts and 3.5 parts, respectively), 30 parts modified polyacrylic acid, 0.3 parts hyperbranched polyesteramine dispersant, 0.2 parts sodium p-styrene sulfonate, 39 parts deionized water, and 25 parts n-propanol.

[0022] The aqueous carbon coating slurry in this embodiment is prepared using the following steps: (1) Weigh 0.3 parts of hyperbranched polyesteramine dispersant using an analytical balance, add 1.95 parts of deionized water, stir evenly to obtain premix A; (2) Weigh 17.55 parts of deionized water and mix it evenly with n-propanol to obtain premixed solution B; (3) Add 40 parts of modified polyacrylic acid, 5 parts of conductive carbon black, 0.5 parts of conductive graphite, and 0.2 parts of sodium p-styrene sulfonate to the mixing tank in sequence, then add 19.5 parts of deionized water and premixed liquid A, disperse at 500 rpm for 40 min to complete the initial premixing and obtain premixed liquid C. (4) Add premixed liquid B to premixed liquid C, stir at 1000 rpm for 60 min, then stir at 1500 rpm for 60 min to mix it evenly, and finally grind it (using zirconia balls with a particle size of 0.5 mm as the grinding medium and grinding at 750 rpm for 2 h) to obtain an aqueous carbon coating slurry with a viscosity of ≤300 mpa.s at 25℃.

[0023] Example 2 The difference between this embodiment and Example 1 is that the water-based carbon coating slurry in this embodiment contains the following components in parts by weight: 0.3 parts conductive graphite, 3 parts conductive carbon black (wherein, the oil absorption value of carbon black A is 210mL / 100g, the oil absorption value of carbon black B is 250mL / 100g, and carbon black A and carbon black B are 1 part and 2 parts respectively), 25 parts modified polyacrylic acid, 0.5 parts hyperbranched polyesteramine dispersant, 0.2 parts sodium dodecylbenzenesulfonate, 39 parts deionized water, and 30 parts n-propanol.

[0024] Example 3 The difference between this embodiment and Example 1 is that the water-based carbon coating slurry in this embodiment contains the following components in parts by weight: 0.6 parts conductive graphite, 5 parts conductive carbon black (of which, the oil absorption value of carbon black A is 180mL / 100g, the oil absorption value of carbon black B is 260mL / 100g, and carbon black A and carbon black B are 1.5 parts and 3.5 parts respectively), 30 parts modified polyacrylic acid, 0.1 parts hyperbranched polyesteramine dispersant, 0.1 parts sodium p-styrene sulfonate, 39 parts deionized water, and 25 parts n-propanol.

[0025] Example 4 The difference between this embodiment and Example 1 is that in this embodiment, the oil absorption value of carbon black A is 200mL / 100g, while the oil absorption value of carbon black A is 230mL / 100g.

[0026] Comparative Example 1 The difference between this comparative example and Example 1 is that the water-based carbon coating slurry in this comparative example contains the following components in parts by weight: 5.5 parts of conductive carbon black (of which, the oil absorption value of carbon black A is 180 mL / 100 g, the oil absorption value of carbon black B is 260 mL / 100 g, and carbon black A and carbon black B are 1.5 parts and 4 parts respectively), 30 parts of modified polyacrylic acid, 0.3 parts of hyperbranched polyesteramine dispersant, 0.2 parts of sodium p-styrene sulfonate, 39 parts of deionized water, and 25 parts of n-propanol.

[0027] Comparative Example 2 The difference between this comparative example and Example 1 is that the water-based carbon coating slurry of this comparative example contains the following components in parts by weight: 0.5 parts conductive graphite, 5 parts conductive carbon black (carbon black A, oil absorption value of 180mL / 100g), 40 parts modified polyacrylic acid, 0.3 parts hyperbranched polyesteramine dispersant, 0.2 parts sodium dodecylbenzenesulfonate, 39 parts deionized water, and 25 parts n-propanol.

[0028] Comparative Example 3 The difference between this comparative example and Example 1 is that the water-based carbon coating slurry in this comparative example contains the following components in parts by weight: 0.5 parts conductive graphite, 5 parts conductive carbon black (carbon black B, oil absorption value 260mL / 100g), 40 parts modified polyacrylic acid, 0.3 parts hyperbranched polyesteramine dispersant, 0.2 parts sodium dodecylbenzenesulfonate, 39 parts deionized water, and 25 parts n-propanol.

[0029] Comparative Example 4 The difference between this comparative example and Example 1 is that the water-based carbon coating slurry in this comparative example contains the following components in parts by weight: 0.5 parts conductive graphite, 5 parts conductive carbon black (of which, the oil absorption value of carbon black A is 180 mL / 100 g, the oil absorption value of carbon black B is 260 mL / 100 g, and carbon black A and carbon black B are 1.5 parts and 3.5 parts respectively), 40 parts modified polyacrylic acid, 0.2 parts sodium dodecylbenzenesulfonate, 39 parts deionized water, and 25 parts n-propanol.

[0030] Test case (1) Settling performance: The water-based carbon coating slurry obtained in the examples and comparative examples was allowed to settle naturally at room temperature, and the settling data was collected within 2 weeks (mainly by collecting the solid content data of the upper and lower layers). Figure 1 The settling diagram of the water-based carbon coating slurry obtained in Example 1 is shown below. Figure 1 The results show that the water-based carbon coating slurry of Example 3 showed almost no significant sedimentation within 14 days of discharge (settling rate of about 7.7%).

[0031] (2) Adhesion test: The water-based carbon coating slurry prepared in the examples and comparative examples was coated on the surface of the corona-treated aluminum foil, and then dried in stages (6s at 90°C and 12s at 130°C) to form carbon-coated aluminum foil. The internal adhesion of the carbon-coated aluminum foil was tested (by the 180° peel test method). Figure 2 The image shows the appearance of the carbon-coated aluminum foil obtained after the adhesion test in Example 3. It can be seen that the 3M tape has no obvious material residue, the carbon-coated aluminum foil surface has no material loss, and the appearance is smooth. The adhesion force of Example 3 was measured to be 402 N / mm.

[0032] (3) Peel strength test: The water-based carbon coating slurry prepared in the examples and comparative examples is coated on the surface of the corona-treated aluminum foil, and then formed by step drying (6s at 90℃, 12s at 130℃) to obtain carbon-coated aluminum foil. The carbon-coated aluminum foil is coated with lithium iron phosphate positive electrode slurry and then dried, and then rolled to obtain an electrode sheet. The peel strength test is performed (obtained by the 180° peel test method, which adopts the electrode sheet pulling method). Figure 3 The test image obtained after peel strength test in Example 3 shows that the carbon-coated aluminum foil performed well in the peel test, with no material loss or breakage, and the test surface was relatively flat.

[0033] (4) Battery Cycle Test: The aqueous carbon-coated slurry prepared in the examples and comparative examples was coated onto the corona-treated aluminum foil surface, and then dried in stages (6s at 90℃, 12s at 130℃) to form carbon-coated aluminum foil. The carbon-coated aluminum foil was coated with lithium iron phosphate positive electrode slurry and dried, and then the resulting electrode sheets were cut by rolling. The cut electrode sheets were wound and combined to form the positive and negative electrodes of the battery (lithium iron phosphate positive electrode, graphite negative electrode), then welded, injected with electrolyte, and charged and discharged to obtain the battery. The battery was cycled at 25℃ for 2000 cycles at room temperature to obtain the battery cycle test diagram. Figure 4 The results of room temperature cycling tests on the batteries prepared in Example 3 and the aluminum foil batteries show that the battery assembled in Example 3 retained 90.86% of its capacity after 2000 cycles at room temperature (1C).

[0034] The performance of the water-based carbon coating slurry and a series of derivative products prepared in the examples and comparative examples were tested, and the test results are shown in Table 1.

[0035] Table 1 Performance Test Results

[0036] As shown in Table 1, the aqueous carbon coating slurry of this invention constructs a highly efficient three-dimensional conductive network through a ternary conductive composite system. The combination of sulfonate dispersant and hyperbranched polyesteramine dispersant significantly optimizes the dispersion effect of solids. Modified polyacrylic acid simultaneously possesses strong dispersibility, long-term stability, and improved interfacial adhesion. Its unique multifunctional groups synergistically solve the three major pain points in aqueous systems: difficulty in dispersing conductive components, easy sedimentation of slurry, and weak coating adhesion. Furthermore, it improves the peel strength of the electrode, reduces the cycle resistance of the battery, and enhances the cycle life of the battery.

[0037] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0038] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A water-based carbon coating slurry, characterized in that, It is prepared from the following components in parts by weight: 0.3-0.6 parts conductive graphite, 3-6 parts conductive carbon black, 20-40 parts modified polyacrylic acid, 0.1-0.5 parts hyperbranched polyesteramine dispersant, 0.1-1 parts sulfonate dispersant, 20-40 parts additives, and 30-40.5 parts solvent; the conductive carbon black comprises carbon black A and carbon black B, the oil absorption value of carbon black A is 180-210 mL / 100 g, and the oil absorption value of carbon black B is 230-260 mL / 100 g; the weight ratio of carbon black A to carbon black B is 3:5-9; the number average molecular weight of the hyperbranched polyesteramine dispersant is 2000-5000 g / mol.

2. The water-based carbon coating slurry according to claim 1, characterized in that, The sulfonate dispersant is one of sodium p-styrene sulfonate, sodium dodecylbenzene sulfonate, or modified lignin sulfonate.

3. The water-based carbon coating slurry according to claim 1, characterized in that, The auxiliary agent is at least one of isopropanol and n-propanol; the solvent is deionized water with a conductivity ≤20μS / cm.

4. The water-based carbon coating slurry according to claim 1, characterized in that, The viscosity of the carbon coating slurry at 25°C is ≤300 mPa·s.

5. A method for preparing an aqueous carbon coating slurry as described in any one of claims 1-4, characterized in that, It includes the following steps: S1. Add the hyperbranched polyesteramine dispersant to the solvent and stir until homogeneous to obtain premix A; S2. Mix the additives with the solvent to obtain premixed solution B; S3. Add conductive graphite, conductive carbon black, modified polyacrylic acid, and sulfonate dispersant to a solvent, then add the premixed solution A and mix evenly to obtain premixed solution C; S4. Add the premixed liquid B to the premixed liquid C, mix evenly, and grind to obtain an aqueous carbon coating slurry; In step S1, the amount of solvent used accounts for 5% of the total amount of solvent used; in step S2, the amount of solvent used accounts for 45% of the total amount of solvent used; and in step S3, the amount of solvent used accounts for 50% of the total amount of solvent used.

6. The method for preparing the water-based carbon coating slurry according to claim 5, characterized in that, In step S4, the grinding is carried out using zirconia balls with a particle size of 0.3-0.5 mm as the grinding medium and at a speed of 650-850 rpm for 2 hours.

7. A carbon-coated aluminum foil, comprising a current collector and a coating disposed on at least one surface of the current collector, characterized in that, The coating is prepared from the aqueous carbon coating slurry according to any one of claims 1-4, or from the aqueous carbon coating slurry prepared by the preparation method according to any one of claims 5-6.

8. A method for preparing carbon-coated aluminum foil as described in claim 7, characterized in that, It includes the following steps: The aqueous carbon coating slurry is applied to the surface of corona-treated aluminum foil, with a coating thickness of 1-2 μm and an areal density ≤0.8 g / m³. 2 Step drying is performed to obtain carbon-coated aluminum foil. The step drying process is as follows: first, infrared drying at 80-100℃ for 5-10 seconds, and then hot air drying at 120-150℃ for 10-15 seconds.

Citation Information

Patent Citations

  • Polyamide nanocomposites with hyper-branched polyetheramines

    CN101977996A

  • Hyperbranched polyester amine and application thereof in water-based coating

    CN110615894A